The key role of sufficiency for low demand-based carbon neutrality and energy security across Europe - Frauke Wiese; Nicolas Taillard; Emile Balembois; Benjamin Best; Stephane Bourgeois; José Campos; Luisa Cordroch; Mathilde Djelali; Alexandre Gabert; Adrien Jacob; Elliott Johnson; Sébastien Meyer; et al. (Nature Communications)
Abstract A detailed assessment of a low energy demand, 1.5 ∘C compatible pathway is provided for Europe from a bottom-up, country scale modelling perspective. The level of detail enables a clear representation of the potential of sufficiency measures. Results show that by 2050, 50% final energy demand reduction compared to 2019 is possible in Europe, with at least 40% of it attributable to various sufficiency measures across all sectors. This reduction enables a 77% renewable energy share in 2040 and 100% in 2050, with very limited need for imports from outside of Europe and no carbon sequestration technologies. Sufficiency enables increased fairness between countries through the convergence towards a more equitable share of energy service levels. Here we show, that without sufficiency measures, Europe misses the opportunity to transform energy demand leaving considerable pressure on supply side changes combined with unproven carbon removal technologies.